2022
DOI: 10.1101/2022.10.31.514555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nascent-Chain Interaction Networks and Their Effect on the Bacterial Ribosome

Abstract: In order to become bioactive, proteins need to be biosynthesized and protected from aggregation during translation. The ribosome and molecular chaperones contribute to both of these tasks. While it is known that some ribosomal proteins (r-proteins) interact with ribosome-bound nascent chains (RNCs), specific interaction networks and their role within the ribosomal machinery remain poorly characterized and understood. Here, we find that RNCs of variable sequence and length (beyond the 1st C-terminal reside) do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 118 publications
0
7
1
Order By: Relevance
“…The presence of noncovalent contacts between RNCs and the L23 r-protein were previously detected for the nascent intrinsically disordered protein (IDP) PIR and for the nascent E. coli globin apoHmpH via a combination of EDC cross-linking and Western blotting. Here, we find that apoMb RNCs display an EDC-cross-linking gel-band pattern qualitatively similar to those of apoHmpH and PIR, as shown in Figure d.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The presence of noncovalent contacts between RNCs and the L23 r-protein were previously detected for the nascent intrinsically disordered protein (IDP) PIR and for the nascent E. coli globin apoHmpH via a combination of EDC cross-linking and Western blotting. Here, we find that apoMb RNCs display an EDC-cross-linking gel-band pattern qualitatively similar to those of apoHmpH and PIR, as shown in Figure d.…”
Section: Resultsmentioning
confidence: 95%
“…While chemical cross-linkers have been previously used to facilitate 3D structure determination of dynamic macromolecules, this approach has not been utilized for RNCs. The zero-length chemical cross-linker EDC has previously been used to identify the interaction of r-proteins with nascent chains, , rendering it an ideal candidate for cross-linking dynamic RNCs to the ribosomal surface. Given that (i) nascent chains only cross-link when they are in close proximity to the ribosome, (ii) prior kinetic studies showed that the majority of nascent chain and r-protein interactions occur very quickly, and (iii) EDC tends to provide an underestimate of the actual populations of interacting RNCs, it is appropriate to regard the cross-linked structure presented here as appropriately capturing the presence of RNC–r-protein contacts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations